Upaya Penanganan Permasalahan Perbatasan Maritim Republik Indonesia - Mahendra Putra Kurnia (Jurnal Risalah Hukum, 2006)
Like most maritime countries, Indonesia has some problems concerning the maritime borders with its neighbouring states. As we know, Indonesia borders on 10 states, both on sea and land. Until now, there are some problems of border, especially maritime borders which have not yet been finished. If these problems are not immediately finished, they will generate problems in the future. As a solution, Indonesian Government can try using a preventive and repressive means. With both efforts, problems of border can be solved. Key words: perbatasan laut (maritime border), preventif (preventive), represif (repressive).